REVIEW OF THE RADIOECOLOGICAL SITUATION IN THE URAL REGION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
A review of the radioecological situation in the Ural region after radiation accidentsat the Mayak Production Association is presented. The results of the work of the staff of theDepartment of Continental Radioecology for assessing the pollution of freshwater ecosystems ofthe Ural region and Western Siberia are shown. The prognostic calculations of the concentrationof radionuclides in the water and bottom sediments of lakes for 100 years, starting in 1957, havebeen performed.
Keywords: radioactive contamination, East Ural radioactive trace, modeling, forecast, Ob, Irtysh, Techa.